2010
DOI: 10.1017/s1751731109991182
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between body energy measured throughout lactation and fertility in dairy cattle

Abstract: The objective of this study was to quantify the genetic association of body energy assessed throughout lactation with a cow's fertility. Nine direct and indirect body energy traits were defined at different stages of lactation. Four were daily records of energy balance, energy content, cumulative effective energy (CEE) and body condition score (BCS) calculated between lactation days 4 and 311. The other five traits included duration of negative energy balance (DNEB), rate of recovery during DNEB (RNEB), sum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 27 publications
7
59
0
Order By: Relevance
“…Body condition score is a subjective measure of the amount of stored fat on the body (Edmonson, et al, 1989;Broster and Broster, 1998), and hence, may be used to indicate energy balance. Banos and Coffey (2010) showed that indirect measures of body energy, such as BCS, have the strongest genetic association with cow fertility (compared with direct measures of body energy). If a genetic evaluation for BCS is to be developed, the trait must be heritable, and the genetic correlations among different parities for BCS should be known.…”
Section: Short Communicationmentioning
confidence: 99%
“…Body condition score is a subjective measure of the amount of stored fat on the body (Edmonson, et al, 1989;Broster and Broster, 1998), and hence, may be used to indicate energy balance. Banos and Coffey (2010) showed that indirect measures of body energy, such as BCS, have the strongest genetic association with cow fertility (compared with direct measures of body energy). If a genetic evaluation for BCS is to be developed, the trait must be heritable, and the genetic correlations among different parities for BCS should be known.…”
Section: Short Communicationmentioning
confidence: 99%
“…Regular evaluation of body reserves facilitates assessment of the cow nutrition regime and feed ration balance, which, in turn, enables to utilise the production potential of cows and obtain optimal milk yields. Body condition monitoring is also important in the prevention of metabolic disorders in the periparturient period and post parturition complications (3). Numerous researchers are of an opinion that the specification of recommended BCS profile of highproducing cows could limit the incidence of a negative energy balance, which is one of the most important causes of the deterioration of fertility indices (9,27).…”
Section: Introductionmentioning
confidence: 99%
“…Direct measures of energy balance are primarily based on individual cow feed intake and milk output (Veerkamp et al, 2000;Hüttmann et al, 2009). However, measurement of individual feed intake is expensive (Veerkamp et al, 2000;Hüttmann et al, 2009) and unfeasible in a commercial population (Banos and Coffey, 2010). Body condition score is a subjective measure of the tissue reserves available on an animal (Edmonson et al, 1989), and is therefore an indicator of energy balance.…”
Section: Introductionmentioning
confidence: 99%
“…Because the body condition can be scored visually on freely moving cattle (Edmonson et al, 1989), it is easy, quick, and inexpensive to measure (Waltner et al, 1994). Last, BCS is moderately to strongly genetically correlated with health (Dechow et al, 2004;Neuenschwander, 2010) and reproduction status (Pryce et al, 2001;Banos and Coffey, 2010;Bastin et al, 2010a,b). In Canada, collection of BCS is part of a routine type classification system, so sufficient data would be available nationwide if a genetic evaluation for this trait were developed.…”
Section: Introductionmentioning
confidence: 99%